2020
DOI: 10.1111/jfbc.13411
|View full text |Cite
|
Sign up to set email alerts
|

A novel peroxidase from runner bean ( Phaseolus coccineus L.): Enhanced affinity purification, characterization, and dye decolorization activity

Abstract: PODs form a large family of enzymes that contain heme groups and use various hydroperoxides as electron acceptors. They catalyze the redox-mediated oxidation reaction of various organic and inorganic compounds (Jin, Li, Long, & Zhang, 2018). The molecular weights of PODs generally range from 30 to 150 kDa, considering the sources from which they are obtained. Plant PODs are divided into three large groups according to the differences in their primary structure. Class I includes intracellular plants, bacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…No study was found on hydroxamic acid molecules on HRP and peroxidase enzymes. In the study by Öztekin and Taşbaşı, 34 the IC 50 value of the bean POD enzyme on the 4‐amino‐3‐bromo 2‐methyl benzohydrazide molecule was 80.3 μM, and the K i value was 71.53 ± 7.59 μM. In the study by Kalın et al., the IC 50 value of the blackradish POD enzyme on the 4‐amino benzohydrazide molecule was 0.726 mM, and the K i value was 0.5947 ± 0.0122 mM, whereas the IC 50 value of the turnip POD was 1.167 mM, and the K i value was 1.1033 ± 0.1016 mM 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No study was found on hydroxamic acid molecules on HRP and peroxidase enzymes. In the study by Öztekin and Taşbaşı, 34 the IC 50 value of the bean POD enzyme on the 4‐amino‐3‐bromo 2‐methyl benzohydrazide molecule was 80.3 μM, and the K i value was 71.53 ± 7.59 μM. In the study by Kalın et al., the IC 50 value of the blackradish POD enzyme on the 4‐amino benzohydrazide molecule was 0.726 mM, and the K i value was 0.5947 ± 0.0122 mM, whereas the IC 50 value of the turnip POD was 1.167 mM, and the K i value was 1.1033 ± 0.1016 mM 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The purification of POD enzymes in one step by the affinity chromatography technique has been investigated in recent studies in the literature. These studies obtained a 10.6% yield from black radish, 9% yield from turnip, 35 37.7% yield from onion roots, 45 56.2% yield from beans, 34 53.6% yield from cowpea, 38 33.8% yield from black radish, and 34.4% yield from sweet radish. 37 In another study by Almaz et al, 39 the HRP enzyme was purified from horseradish in a single step by the affinity chromatography technique using 23 different amino benzohydrazide-based ligands.…”
Section: Purification Of the Hrp Enzyme By Affinity Chromatographymentioning
confidence: 97%
See 1 more Smart Citation
“…K M and V max values for guaiacol were reported by the authors to be 24.88 mM and 3.23 EU/mL.min for black radish POD, [13] and 17.35 mM and 1234 EU/mL.min for leaves of spinach POD, [30] respectively. Additionally, these values for hydrogen peroxide were declared by the authors as 12.49 mM and 4.055 EU/mL.min for turnip POD, [13] and 1.37 mM and 7.61 EU/mL.min for runner bean POD, [31] respectively. The K M value is a measure of the stability of the enzyme‐substrate complex.…”
Section: Resultsmentioning
confidence: 99%
“…Then, p-aminobenzoic acid (20 mg) was diazolated and was coupled to average 2 g of Sepharose 4B-L-tyrosine (dry weight). At the end of this reaction, the formed affinity gel was washed and loaded into the 1 × 10 cm column (Aksoy, 2020;Oztekin & Tasbasi, 2020). The column was equilibrated with 0.05 M pH 6.0 phosphate buffer (PBS) and the supernatant was applied.…”
Section: Affinity Chromatographymentioning
confidence: 99%